Asymmetric synthesis of CF2-functionalized aziridines by combined strong Brønsted acid catalysis - Tan, Xing-Fa; Zhang, Fa-Guang; Ma, Jun-An (Beilstein Journal of Organic Chemistry, 2020)
A diastereo- and enantioselective approach to access chiral CF2-functionalized aziridines from difluorodiazoethyl phenyl sulfone (PhSO2CF2CHN2) and in situ-formed aldimines is described. This multicomponent reaction is enabled by a combined strong Brønsted acid catalytic platform consisting of a chiral disulfonimide and 2-carboxyphenylboronic acid. The optical purity of the obtained CF2-substituted aziridines could be further improved by a practical dissolution–filtration procedure.
Keywords: aziridines; chiral disulfonimides; difluoromethyl compounds; fluorinated diazo reagents; strong Brønsted acids